Zircon Th/U ratios in magmatic environs - Kirkland, Chris; Smithies, R.; Taylor, Richard; Evans, Noreen; McDonald, B. (Elsevier, 2015)
A comprehensive database of zircon composition in West Australian magmatic rocks reveals negative correlations between both U and Th zircon/whole rock ratio and the zircon saturation temperature, with the observed change with temperature less for U(zircon/whole rock) than for Th(zircon/whole rock). This observation implies a systematic increase in the zircon/rock ratio with falling crystallisation temperature, a result which replicates findings from experimental partition coefficient studies. Under equilibrium conditions there is a trend to lower zircon Th/U with increasing melt temperature which can be attributed to lattice strain. However, within a fractionating magma, Ti-in-zircon temperatures yield the opposite relationship of lower zircon Th/U in cooler melts. This is due to zircon growth under non-equilibrium conditions with greater incompatibility of Th relative to U, and the removal and segregation of mineral precipitates. These observations can be used as a tool to determine whether zircon growth was in a liquid of similar composition to the observed whole rock. We present an equation that estimates the degree of fractionation between the whole rock composition and the zircon parental liquid. This parameter demonstrates the dissimilarity between the liquid from which the zircon grew and the whole rock composition and aids in distinguishing mesostasis growth in fractionated melt versus cumulate growth in less fractionated magma. We use this ratio to investigate zircon growth in igneous rocks of the Musgrave Province. For a suite of c. 1200Ma magmas that become progressively more fractionated, based on whole rock La/Sm, the fractionation index demonstrates increasing compositional differences between the whole rock and the zircon growth liquid. In the most extreme case independent petrographic evidence indicates mesostasis growth of zircon, whereas in the least fractionated melt zircon growth is established to be close to equilibrium with a zircon saturation temperature of c. 900°C likely being accurate. In contrast, zircon crystals from a rhyolite of the c. 1070Ma Giles Supervolcano have distinctive compositional discordances indicative of antecrystic components. The fractionation factor in this rock implies some zircon growth under higher temperature conditions than the whole rock zircon saturation temperature.